PDE0305: Implementation of the “First Friendly Practice for Transfemale People” at Arzobispo Loayza National Hospital. A public-private partnership, Lima, Peru 2019 - Muñoz, M. (2020)
Trans-gender population is considered at high risk for HIV infection due to multiple factors. AHF Peru works with trans-female population since 2013, and since 2017, has implemented a “friendly” external consultant for Trans- female patients at Arzobispo Loayza National Hospital (HNAL), with a high impact in the attention of the HIV Trans-Female population.